2006
DOI: 10.1002/cncr.21917
|View full text |Cite
|
Sign up to set email alerts
|

FISH detection of t(14;18) in follicular lymphoma on Papanicolaou-stained archival cytology slides

Abstract: Objective Antibodies to glutamic acid decarboxylase (GAD) have been described in a few patients with temporal lobe epilepsies consistent with limbic encephalitis (LE). We studied a cohort of patients with recent‐onset temporal lobe epilepsy caused by LE to test for GAD antibody positivity and response to immunotherapies. Methods Over a period of 3.75 years, 138 patients aged ≥18 years investigated at the Department of Epileptology, University of Bonn, for recent‐onset epilepsy were prospectively collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
(51 reference statements)
1
27
1
1
Order By: Relevance
“…1, 2). These tests provide useful information regarding clonality, or distinctive chromosomal/molecular abnormalities associated with specific entities and lymphoid cell lineages, confirming NHL diagnosis - albeit with some exceptions and limitations [5,9,10,11,12,13,14,15,16,17,18]. Classical cytogenetics include the routine analysis of G-banded chromosomes and other cytogenetic banding techniques for the study of cell structure and chromosomes.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…1, 2). These tests provide useful information regarding clonality, or distinctive chromosomal/molecular abnormalities associated with specific entities and lymphoid cell lineages, confirming NHL diagnosis - albeit with some exceptions and limitations [5,9,10,11,12,13,14,15,16,17,18]. Classical cytogenetics include the routine analysis of G-banded chromosomes and other cytogenetic banding techniques for the study of cell structure and chromosomes.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…Cytogenetics or FISH can be used to identify lymphomas with characteristic chromosomal translocations, including follicular lymphoma (FL) [t(14;18)], mantle-cell lymphoma [t(11;14)], Burkitt's lymphoma [t(8;14)], and anaplastic T-cell lymphoma [t(2:5)], for example. FISH testing can be performed on cell block sections as well as on cytology smears similar to tissue specimens [24,46,47]. Molecular PCR tests of B- and T-cell gene arrangement can be performed when the clonality by FC is inconclusive.…”
Section: Fna Diagnosis Of Deep-seated Lymphomas Via Eus/ebus Emphasimentioning
confidence: 99%
“…Studies have shown that FNA material has the advantage of providing higher-quality DNA. Many studies have demonstrated that cytogenetics as well as newer molecular techniques can be performed on smear specimens [24,46,47]. …”
Section: Lymphoma Subclassification Using Eus/eus-fnamentioning
confidence: 99%
“…FISH analysis can be performed on cytologic material, allowing maximum use of small diagnostic samples. It requires a priori knowledge of a suspected aberration, however, and depends on the availability of probes 3,19,20 (Table 3). Cytogenetic studies, especially FISH, are particularly helpful in distinguishing (Fig.…”
Section: Lymphomasmentioning
confidence: 99%